Respuesta :

Step-by-step explanation:

I think you made some mistakes in the problem definition.

I guess you mean

9 = (1/27)^(a+3)

let's think about how to create 9 out of 1/27 just by using exponents.

we note that 27 is 3³. and therefore the cubic root of 27 is 3.

so,

(1/27)^(1/3) = 1/3

because the exponent 1/3 means "cubic root". an exponent 1/2 means square root. and so on.

making the exponent negative means 1/...

so,

(1/27)^(-1/3) = 3

and now, with what exponent operation can we turn 3 into 9 ?

by squaring it.

so,

((1/27)^(-1/3))² = 9

putting an exponent on an exponent means to multiply the exponents during simplification.

therefore,

((1/27)^(-1/3))² = (1/27)^(-2/3) = 9

that means

a + 3 = -2/3

a = -2/3 - 3 = -2/3 - 9/3 = -11/3

so, the first answer option is correct.